2013
DOI: 10.1007/s11207-013-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Observable Effects of Interplanetary Coronal Mass Ejections on Ground Level Neutron Monitor Count Rates

Abstract: In this work, non-recurrent Forbush decreases (FDs) triggered by the passage of shock-driven interplanetary coronal mass ejections (ICMEs) have been analyzed. Fifty-nine ICMEs have been studied but only the 25% of them were associated to a FD. We find that shock-driving magnetic clouds (MCs) produce deeper FDs than shock-driving ejecta. This fact can be explained regarding to the observed growing trends between decreases in neutron monitor (NM) count rate and MC/ejecta speed and its associated rigidity. MCs ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
(45 reference statements)
3
23
0
Order By: Relevance
“…This discrepancy arises because Jordan et al (2011) analysed a set of ICMEs both with and without an MC inside an ICME, while in this work we focus on MCs. The comparison is an even poorer match for the 25% obtained by Blanco et al (2013) from a pool of 59 shock-driving ICMEs from January 1997 to September 2006. Still, in this list only 24 MCs were detected and eight of them (33%) produced an observable FD at ground-level neutron monitors.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…This discrepancy arises because Jordan et al (2011) analysed a set of ICMEs both with and without an MC inside an ICME, while in this work we focus on MCs. The comparison is an even poorer match for the 25% obtained by Blanco et al (2013) from a pool of 59 shock-driving ICMEs from January 1997 to September 2006. Still, in this list only 24 MCs were detected and eight of them (33%) produced an observable FD at ground-level neutron monitors.…”
Section: Discussionmentioning
confidence: 77%
“…Still, in this list only 24 MCs were detected and eight of them (33%) produced an observable FD at ground-level neutron monitors. All events in Blanco et al (2013) were recorded at 1 AU while the events presented in this work were detected at heliocentric distances below 1 AU. This clear difference could be explained if the MC location plays a role for the FD depth, which deeper when the MC is closer to Sun.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, other studies (e.g., Badruddin et al 1986;Sanderson et al 1990;Kuwabara et al 2009) have concluded that magnetic clouds can make an important contribution to FDs. There have been recent conclusive associations of FDs with Earth-directed CMEs (Blanco et al 2013;Oh & Yi 2012). Cane (2000) introduced the concept of a two-step FD, where the first step of the decrease is due to the shock and the second step is due to the ICME.…”
Section: Introductionmentioning
confidence: 99%